Prairie Urbanism - Garth Rockcastle (Oz, 1986)
It can be argued that there is oftentimes an intrinsic formal beauty latent in midwestern cities, especially the smaller ones. Why no great architects, at least to my knowledge, have pursued making this beauty more apparent or manifest is most unfortunate...